Sosialisasi Penerapan Sila ke Dua Kemanusian yang Adil dan Beradab di MI Al-Misbah - Putri, Astian; Ali, Adlan; Fauziyah, Salwa; Satria, Maulana; Hakim, Muhammad Taufiqul; Kamil, Muhammad; Maulida, Putri Zahra; Setiadi, Aneza Putri; Aliyah, Rosmatun; Sri, Neng; Ikyan, Adzka; Herdiana, Dian (Universitas Negeri Gorontalo, 2025)
The second principle of Pancasila,